Analysis of Shelf Power of Snake Fruit Varieties at Room Temperature - Zulia, Ida; Hartanti, Dyah Ayu Sri; Puspaningrum, Yessita (LPPM Universitas KH. A. Wahab Hasbullah, 2024)
Snake fruit is a horticultural plant that has many enthusiasts and cultivators in Indonesia. There are many varieties and post-harvest storage methods for snake fruit. This research used 3 varieties of snake fruit, namely pondoh snake fruit, bali snake fruit, and keras snake fruit, which were stored at room temperature. The research method uses descriptive analysis to draw conclusions regarding important points in the research. This research shows that when storing 3 varieties of snake fruit at room temperature, the condition of the snake fruit skin has a big impact on shelf life, because thicker snake fruit skin is more susceptible to physical damage and fungal or bacterial infections. The results of this research bali snake fruit show that it has the longest shelf life at room temperature, around 12 days until spoilage, pondoh snake fruit 9 days, and keras snake fruit 6 days. This is because bali snake fruit has thicker skin than the other two snake fruit.